MEDIA PEMBELAJARAN DIGITAL : PENTINGKAH UNTUK MENINGKATKAN HASIL BELAJAR SISWA SEKOLAH DASAR? - Senja Wijaya, Eva Dwi; Susongko, Purwo; Nafiati, Dewi Amaliah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
Natural and Social Sciences (IPAS) learning at the elementary level often faces challenges, especially in delivering abstract concepts such as plant reproduction. Conventional materials such as textbooks and worksheets are often insufficient in providing meaningful and engaging learning experiences. This study aims to analyze the need for developing digital-based IPAS teaching materials using interactive digital media as a contextual and multimodal solution that encourages active student participation. The research employed an exploratory descriptive method with a mixed-methods approach, combining both quantitative and qualitative data. Samples were selected using proportional cluster random sampling, involving teachers, students, school principals, and parents in Pemalang Regency. Data were collected through Likert-scale questionnaires and in-depth interviews and analyzed descriptively. The findings indicate a high demand among all respondent groups for technology-based IPAS learning materials that are visual, interactive, and easy to understand. Teachers found interactive digital media to be relevant and user-friendly, allowing for engaging content delivery through text, images, video, and audio. Principals expressed full support for the development of such media in alignment with the Merdeka Curriculum. Parents showed enthusiasm and a willingness to assist their children in using digital tools. Students reported increased motivation and better comprehension when learning was supported by multimodal and interactive media. In conclusion, developing IPAS teaching materials based on interactive digital media is essential to meet the demands of 21st-century learning and to enhance student engagement, understanding, and learning outcomes in elementary education.